POTENTIAL OF ASSESSMENT PROCEDURES TO ENHANCE LEARNING OUTCOMES - Tayyiba Asim Muhammad Asim; Farah Naeem; Aimen Yousaf (Taez University, 2024)
The concern for the assessment of learning outcomes is reinforced today by the requirement expressed by society to get hold of skills graduates in various fields of activities. Hence, Learning outcomes are considered as an essential part of any type of learning process. A learning outcome is a clear statement of what a learner is expected to be able to do, or to know about language and provide value at the completion of a unit of study, and finally how well they should be expected to achieve those outcomes. It states both the substances of learning and how its attainment is to be demonstrated. This study will enhance the importance of assessment procedures of learning outcomes in developing higher education students' information literacy competence which should be valued in all the fields of life. The study will find different types of tools and methods which can evaluate knowledge and skills to evaluate the importance of assessment. By using different types of assessment activities, teachers can improve activities of evaluations that is an important part of assessment procedures to achieve the learning outcomes. A central objective in the university context is to promote innovative teaching activities that increasingly see students as an active part of the learning process, fostering their learning outcomes, knowledge, and skills. Innovative assessment practices have the potential to shift the way universities function. By focusing on well-designed assessment tasks, where students are expected to work collegially and are actively involved in assessment, the opportunity to engage students in the assessment process is realized. For the purpose of finding out the potential of assessment procedures in developing learning outcome, one of the courses taught in English Department of Punjab University, Pakistan to the BS Linguistic students is assessed. The findings of the study reveal that assessment of learning outcomes today becomes an integral part of teaching and learning process, though whatever methods or tools we use to evaluate students' performance of knowledge or cognitive skills, it should be in a positive and encouraging way of assessment. Moreover, the use of different assessment activities clearly points out that the achievement of learning outcomes depends on the proper use of assessment tools, then only we can see the potential of assessment in enhancement of learning outcomes.